2021
DOI: 10.3390/polym13081334
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Barrier Properties of Packaging Paper by Polyvinyl Alcohol Based Polymer Coating—Effect of the Base Paper and Nanoclay

Abstract: The poor barrier properties and hygroscopic nature of cellulosic paper impede the wide application of cellulosic paper as a packaging material. Herein, a polyvinyl alcohol (PVA)-based polymer coating was used to improve the barrier performance of paper through its good ability to form a film. Alkyl ketene dimer (AKD) was used to enhance the water resistance. The effect of the absorptive characteristics of the base paper on the barrier properties was explored, and it was shown that surface-sized base paper prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 30 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, there is less variation in the thickness of the uncured two-pass systems when compared to the single-pass systems. Previous studies have also found that “double coating” (i.e., two passes) has improved barrier properties on cellulosic substrates . PEI:PAA:KAO 2 uncured and buffer cured coatings exhibit the best OTR performance at 126,000 and 550,000 cc/(m 2 ·day·atm), respectively.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, there is less variation in the thickness of the uncured two-pass systems when compared to the single-pass systems. Previous studies have also found that “double coating” (i.e., two passes) has improved barrier properties on cellulosic substrates . PEI:PAA:KAO 2 uncured and buffer cured coatings exhibit the best OTR performance at 126,000 and 550,000 cc/(m 2 ·day·atm), respectively.…”
Section: Resultsmentioning
confidence: 86%
“…Despite these benefits, paper-based packaging typically exhibits high oxygen transmission rate (OTR) due to its porous structure. This porosity can lead to severely accelerated food spoilage due to oxidation and microbial growth. , It is for this reason that little effort has been placed on implementing paper-based packaging more widely. In an effort to improve the utility of paper, a multitude of barriers have been added to cellulosic substrates. Even so, more work is needed to improve the barrier properties of paper.…”
Section: Introductionmentioning
confidence: 99%
“…Materials formed with five and three layers of coatings, except for COA11 (C CH = 1.0%, C AP = 1.8%, C AC = 0.2, NL = 5) and COA15 (C CH = 1.0%, C AP = 1.8%, C AC = 1.2, NL = 5), showed high Abs, which could be associated with the hydrophilic nature of chitosan. The paper’s hygroscopic matrix reduces the material’s mechanical properties (resistance) in the presence of water [ 49 ]. According to Bordenave et al [ 50 ], chitosan coating maintains the hydrophilic characteristic of paper, even at low concentrations, and is responsible for controlling the interactions with water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the deposition of functional bio-based coatings is a promising approach to improving the surface characteristics of substrates (i.e., adhesion, wettability, water repellence, anti-corrosion, antioxidant, antimicrobial and gas barrier properties) without compromising the biodegradable and/or recyclable features [ 17 ]). Polymeric coatings based on chitin nanofibrils, chitosan or PLA-based composites demonstrated their effectiveness for antimicrobial packaging [ 18 , 19 , 20 , 21 , 22 , 23 ]; hydrophobic properties can be imparted by including chitin or waxes [ 24 , 25 , 26 ] or by acrylic-modified crosslinkable chitosan nanocoatings [ 27 ]; among efficient oxygen-barrier layers, crosslinked proteins [ 28 , 29 , 30 , 31 , 32 ], cellulose nanocrystals [ 33 , 34 , 35 ] and poly(vinyl alcohol) [ 36 , 37 , 38 , 39 , 40 ] have recently received attention due to their excellent barrier performance.…”
Section: Introductionmentioning
confidence: 99%